السرد الشعبي وتحولات أسئلة المنهج من مورفولوجيا فلاديمير بروب إلى بنيوية شتراوس - عداد, راضية; لراوي, العلمي (جامعة الوادي - University of Eloued, 2023)
ملخص:يأتي هذا الموضوع كمطلب ملحّ إزاء فهم وتطبيق المناهج النقدية على النصوص عموما والسرد الشعبي خصوصا من منطلق أنّ الباحث في الدراسات الأدبية أصبح يجنح إلى آليات الاستقراء والتحليل والوصف هروبا من الغوص في المضامين والأنساق، رغم أنّ قراءة النّص تقبل معظم التأويلات طالما يحلل النّص في مضامين قرائية متعددة تفتح المجال لفهمه واستيعابه، ولعلّ من الدراسات التي أسهمت في تطوير منهجية التحليل لخصوصيات السرد باختلاف أشكاله نجد ما قدّمه كلّ من "بروب" في مورفولوجيا الحكي العجائبي، ومقاربة الأسطورة لدى شترواس حيث شكلا توجها بنيويا اتخذ من بنية النّص بعدا تحليليا لفك شفرات ومغالق السرود الأدبية. الكلمات المفتاحية: السرد الشعبي، البنائية،مورفولوجيا الحكاية،الأسطورة. Abstract: This topic comes as an urgent demand for understanding and applying critical approaches to narrative texts in general and popular narratives in particular,this study bases on the fact that research in literary studies has become inclined to the mechanisms of extrapolation analyses and description to escape from immersion in contents and formats, although reading the text accepts most interpretations as long as it is analyzed in reading contents that open the way for understanding it ;Perhaps among the studies that contributed to the development of methodology for the analysis of the spicifics of the narrative in its various forms,we find what Vladimir Propp presentin " the morphology of Myth" and the structural approach and structural approach to the legend of Strauss,where they formed a structural approach that took the structure of the text as an analytical dimensions to decipher the codes and closures of popular narrative in particular . Key words: : popular narrative,structuralism,fable morphology,the legend
مقال
Keywords: السرد الشعبي ; البنائية ; مورفولوجيا الحكاية ; الأسطورة